The Influence of Fraud Diamond on Academic Fraud Intention Among Accounting Students - David Pesudo; Vrilita Vanesa Parengkuan (Politeknik Negeri Madiun, 2023)
This study was aimed to find out the influence of fraud diamond, including pressure, opportunity, rationalization, and ability on students' academic cheating intentions. Quantitative method was used to carry out this study. The population of this study included students from the Accounting Study Program, Faculty of Economics and Business, Samratulangi University, Manado, as the population, and the samples included the classes of 2019 students in the major, chosen by using purposive sampling. The data was in the form of primary data obtained by distributing questionnaire through the Google form. The research results have shown that partially, the pressure variable has no effect on students' academic cheating intentions, opportunity has a negative effect on academic cheating intentions, rationalization does not have a positive effect on students' academic cheating intentions, and ability affects positively on academic cheating intentions. After conducting the research, it is suggested that future researchers are expected to be able to further develop other factors to be studied, including adding other factors from variables that can influence students' intentions to commit academic fraud such as ability, motivation and integrity.